ANALISIS PENGARUH DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT - B01109027, FITRIA RATNASARI (Jurnal Pembangunan dan Pemerataan, 2014)
The title of the study is " The Effect Analysis of Fund Balance Against Economic Growth in District / City of West Kalimantan Province " . The purpose of this study is to analyze the effect of Fund Balance to Economic Growth in District / City of West Kalimantan Province . The data used in this study is a secondary data , the type of panel data Regency / City 2009-2011 period ( 3 years ) were obtained from the Bureau of Finance and the Central Bureau of Statistics . Data processing includes statistical test using the computer program Eviews - 6 and economics test . The results of this study showed that the Balance Fund has a positive and significant impact on economic growth in the District / City of West Kalimantan Province . This means that the balance funds have been able to provide its influence on economic growth through capital expenditures for infrastructure development . The coefficient of determination ( R2 ) of 0.067015 means the amount of influence exerted by the variable Fund Balance to Economic Growth in District / City of West Kalimantan Province is at 6.70% which means the Fund Balance variables affect the economic growth of 6.70% . While the remaining 93.3 % is influenced by other factors such as science and technology . Keywords : Fund Balance and Economic Growth